Sistem Informasi Pelayanan Pemasangan Listrik Pada PT. PLN ULP Medan Baru Berbasis Web - Hasyifah Sibarani, Fathiya; Maharani Tanjung, Sunilfa; Abdillah, Muhammad Oemar (Jurnal Ilmiah Sains dan Teknologi, 2024)
PT. PLN ULP Medan Baru is part of a State-Owned Enterprise that focuses on the Customer Service Unit. Currently customers are already using the PLN Mobile application, but some customers still come to the office directly to submit complaints and complaints regarding the condition of electricity in their homes. The PLN Mobile application sometimes experiences errors when making complaints, some users may face problems if the application is not compatible with the current version. This research aims to develop a web-based information system that makes it easier for customers to process complaints, requests for new installations, power changes and migration. The results of this research produced an information system for Electrical Installation Services at PT. PLN ULP Medan Baru, which aims to make it easier for customers to report complaints or problems related to electricity where they live.